Analyzing Elementary School Student Cooperative Skill through Outbound Activity - Nur, Lutfi (TEGAR: Journal of Teaching Physical Education in Elementary School, 2020)
Cooperation is an important aspect to be owned by students to support their quality of life. The purpose of this study was to find out elementary school student cooperative skills through outbound activity. The descriptive method was chosen to describe the cooperative ability of 20 lower-class students, aged 7-9 years. The data were collected through an electronic instrument of cooperative rubric covering three aspects, including communication, responsibility, and helping each other. The obtained data were analyzed by using descriptive statistical analysis to describe the cooperative level of the students in the outbound activity. The result of the study showed that the student cooperative skill was very low. It was shown by the development of the score. The score on the communication aspect was 44%. The score on the responsibility aspect was 29%. The score on helping each other was 33%. This condition should become an evaluation for the elementary school teachers to find out an alternative solution to overcome the problems. In addition, technology utilization, such as electronic rubric, could help teachers in conducting observation to evaluate the student’s learning development in elementary schools.